Creating learning communities : - Shapiro, Nancy S. (Jossey-Bass Publishers, 1999)
One of the most powerful ideas in higher education today is transforming campuses into learning communities. At last, Shapiro and Levine have given us--faculty, students, and administrators--a handbook on how to accomplish this. It is one of those too rare and much-needed volumes on translating theory into practice by authors who have actually done it."